Synthesis of In‐House Produced Calibrated Silver Phosphate with a Large Range of Oxygen Isotope Compositions. Issue 4 (5th August 2019) - Lécuyer, Christophe; Fourel, François; Seris, Magali; Amiot, Romain; Goedert, Jean; Simon, Laurent
Abstract : The large range of stable oxygen isotope values of phosphate‐bearing minerals and dissolved phosphate of inorganic or organic origin requires the availability of in‐house produced calibrated silver phosphate of which isotopic ratios must closely bracket those of studied samples. We propose a simple protocol to synthesise Ag3 PO4 in a wide range of oxygen isotope compositions based on the equilibrium isotopic fractionation factor and the kinetics and temperature of isotopic exchange in the phosphate–water system. Ag3 PO4 crystals were obtained from KH2 PO4 that was dissolved in water of known oxygen isotope composition. Isotopic exchange between dissolved phosphate and water took place at a desired and constant temperature into PYREX™ tubes that were placed in a high precision oven for defined run‐times. Samples were withdrawn at desired times, quenched in cold water and precipitated as Ag3 PO4 . We provide a calculation sheet that computes the δ 18 O of precipitated Ag3 PO4 as a function of time, temperature and δ 18 O of both reactants KH2 PO4 and H2 O at t  = 0. Predicted oxygen isotope compositions of synthesised silver phosphate range from −7 to +31‰ VSMOW for a temperature range comprised between 110 and 130 °C and a range of water δ 18 O from −20 to +15‰ VSMOW. Key Points: Ag3 PO4 crystals are obtained from KH2 PO4 dissolved in water of known δ 18 O. Precipitation takes place at temperatures between 110 °C and 130 °C δ 18 O of synthesized silver phosphate cover a 40‰ range.